1996
DOI: 10.1136/jcp.49.2.120
|View full text |Cite
|
Sign up to set email alerts
|

Lipoproteins in pregnant women before and during delivery: influence on neonatal haemorheology.

Abstract: Aims-To investigate whether the lipid profile of pregnant women during parturition differs from the profile at previous stages of pregnancy and to determine the effects of maternal lipid changes on fetal or neonatal haemorheology. Methods-Sixty pregnant women were studied, divided into two groups. Group 1 contained 30 women ofmean age of27 (SD 3) years and gestational age >38 weeks in whom delivery had not yet begun; all these pregnancies followed an uncomplicated course and there was no evidence of any fetal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

1998
1998
2002
2002

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 16 publications
0
0
1
Order By: Relevance
“…2 , demonstrating that increased fetal serum lipid levels are attributable to increased mobilisation of lipids from fat stores. Our results disagree with the report by Uberos‐Fernández et al 17 , demonstrating the similar maternal and fetal serum‐free fatty acid levels and the significantly lower fetal serum triglyceride levels. Thus, they concluded that transplacental movement of free fatty acid from mother to fetus is important.…”
Section: Discussioncontrasting
confidence: 99%
“…2 , demonstrating that increased fetal serum lipid levels are attributable to increased mobilisation of lipids from fat stores. Our results disagree with the report by Uberos‐Fernández et al 17 , demonstrating the similar maternal and fetal serum‐free fatty acid levels and the significantly lower fetal serum triglyceride levels. Thus, they concluded that transplacental movement of free fatty acid from mother to fetus is important.…”
Section: Discussioncontrasting
confidence: 99%